Strengthening Destination Management Organization for Community-Based Tourism Development: Evidence from Sawahan Village, Trenggalek Regency, Indonesia - Rahaju, Tjijik; Ardiyansah; Azhari, Yolanda Jihan; Jaharudin, Haris Zuan (Yayasan Sinergi Kawula Muda, 2026)
Destination Management Organizations (DMOs) play an important role in coordinating stakeholders and strengthening tourism governance, yet many rural destinations continue to experience fragmented institutions, limited managerial capacity, and weak integration of local communities. This study examines how strengthening a village-level DMO contributes to community-based tourism development in Sawahan Village, Trenggalek Regency, an emerging rural destination characterized by waterfall ecotourism and community-managed services. Using a qualitative case study approach, data were collected through in-depth interviews with 15 key informants, supported by field observations and document analysis, and analyzed using thematic analysis to identify governance patterns and community outcomes. The findings show that institutional strengthening led to more structured coordination, evidenced by the formation of formal tourism management units and the implementation of routine coordination meetings among stakeholders. In addition, the adoption of digital-based promotion, particularly through social media platforms managed by local operators, increased destination visibility as reflected in more consistent monthly visitor flows reported by tourism managers. Community participation also expanded, as local residents became directly involved in homestay provision, guiding services, and micro-scale tourism enterprises, indicating observable changes in local economic engagement rather than solely perceived benefits. These results demonstrate that clearer institutional roles, improved coordination mechanisms, and inclusive participation practices contribute to more effective and locally grounded tourism governance. This study offers an empirical contribution by showing how DMO strengthening at the village level translates governance principles into practical outcomes, while highlighting the importance of context-specific institutional capacity building for sustainable rural tourism development.